Two new species of the bee-mimicking genus Mallophora (Diptera, Asilidae) from Colombia - Yepes, Sol; Forero, Dimitri (Zootaxa, 2021)
Mallophora Macquart, 1834 is a bee-mimicking genus of Asilidae, which has more than 50 described species in the Neotropical Region. Examination of specimens of this genus from Colombia indicate that there are two undescribed species based on the structure of the hind leg of males. Here we describe Mallophora gauteovan sp. nov. and Mallophora kalos sp. nov. from Tayrona National Park (Magdalena) and Arauca, respectively. For each new species a diagnosis and a description including the structure of the face, thorax, male hind leg, abdomen, and hypandrium are provided. All morphological structures are documented with digital photographs.